2017
DOI: 10.3892/ol.2017.7198
|View full text |Cite
|
Sign up to set email alerts
|

Metformin enhances the chemosensitivity of hepatocarcinoma cells to cisplatin through AMPK pathway

Abstract: This study investigated the effect of metformin on chemosensitivity of hepatocarcinoma cells to cisplatin and the possible mechanism. HepG2 and Huh-7 hepatoma cells were treated with cisplatin at concentrations of 0, 2, 4, 6, 8 and 10 µM for 48 h. Proliferation of HepG2 and Huh-7 hepatoma cells were detected by MTT assay. Apoptosis of hepatocellular carcinoma cells was detected by flow cytometry. Western blot analysis was used to detect the expression of 5-monophosphate-activated protein kinase (AMPK) and p-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Combined application of metformin and cisplatin had shown controversial results in the treatment of various tumors. It has been reported that metformin could promote the anticancer effect of cisplatin in breast cancer ( 18 ), NSCLC ( 26 ), nasopharyngeal carcinoma ( 20 ), liver cancer ( 27 ). On the contrary, metformin reduced the anti-proliferative effects of cisplatin through mTOR/AKT signaling pathways in the MKN-45 cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined application of metformin and cisplatin had shown controversial results in the treatment of various tumors. It has been reported that metformin could promote the anticancer effect of cisplatin in breast cancer ( 18 ), NSCLC ( 26 ), nasopharyngeal carcinoma ( 20 ), liver cancer ( 27 ). On the contrary, metformin reduced the anti-proliferative effects of cisplatin through mTOR/AKT signaling pathways in the MKN-45 cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2831] In addition, various preclinical studies have found that metformin enhances the anti-tumor effects of platinum and increases their sensitivity by regulating multiple signaling pathways including AMPK-mTOR, ERK1/2, NF-κB. [3234] Thus, we hypothesized that metformin might benefit lung cancer patients who received platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Wide differences in its effectiveness also stems from the variety of clinical approaches used for drug delivery [8][9][10]. Thus, optimisation of cisplatin efficiency [11,12] and minimisation of cisplatin chemoresistance [13] are the most important approaches that could improve patient treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%